Why Deliberative Democracy? - Gutmann, Amy (Princeton University Press, 2009)
The most widely debated conception of democracy in recent years is deliberative democracy--the idea that citizens or their representatives owe each other mutually acceptable reasons for the laws they enact. Two prominent voices in the ongoing discussion are Amy Gutmann and Dennis Thompson. In Why Deliberative Democracy?, they move the debate forward beyond their influential book, Democracy and Disagreement. What exactly is deliberative democracy? Why is it more defensible than its rivals? By offering clear answers to these timely questions, Gutmann and Thompson illuminate the theory and practice of justifying public policies in contemporary democracies. They not only develop their theory of deliberative democracy in new directions but also apply it to new practical problems. They discuss bioethics, health care, truth commissions, educational policy, and decisions to declare war. In "What Deliberative Democracy Means," which opens this collection of essays, they provide the most accessible exposition of deliberative democracy to date. They show how deliberative democracy should play an important role even in the debates about military intervention abroad. Why Deliberative Democracy? contributes to our understanding of how democratic citizens and their representatives can make justifiable decisions for their society in the face of the fundamental disagreements that are inevitable in diverse societies. Gutmann and Thompson provide a balanced and fair-minded approach that will benefit anyone intent on giving reason and reciprocity a more prominent place in politics than power and special interests
Description based on online resource; title from PDF title page (publisher's Web site, viewed Mar. 21, 2016)
Keywords: Compromise (Ethics); Democracy; Political ethics; Representative government and representation; Deliberative Demokratie